2022
DOI: 10.1111/ejn.15661
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of blood and brain‐derived ageing and inflammation‐related DNA methylation signatures and their association with microglial burdens

Abstract: Inflammation and ageing-related DNA methylation patterns in the blood have been linked to a variety of morbidities, including cognitive decline and neurodegenerative disease. However, it is unclear how these blood-based patterns relate to patterns within the brain and how each associates with central cellular profiles. In this study, we profiled DNA methylation in both the blood and in five post mortem brain regions (BA17, BA20/21, BA24, BA46 and hippocampus) in 14 individuals from the Lothian Birth Cohort 193… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…This increase could also be in response to Aβ burden although higher levels of GFAP burdens seen in hippocampus regions across all cohorts do not mirror Aβ burdens in the same region comparison suggesting other factors were at play. Previous studies investigating DNA methylation signatures in the LBC1936 cohort have indicated CD68 burdens are highest in the hippocampal brain region [36]. Here we again show evidence of this neuroimmune response; however, we also highlight significant cohort variation although burden levels were relatively low and below 0.5% for all regions apart from the hippocampus.…”
Section: Discussionsupporting
confidence: 72%
“…This increase could also be in response to Aβ burden although higher levels of GFAP burdens seen in hippocampus regions across all cohorts do not mirror Aβ burdens in the same region comparison suggesting other factors were at play. Previous studies investigating DNA methylation signatures in the LBC1936 cohort have indicated CD68 burdens are highest in the hippocampal brain region [36]. Here we again show evidence of this neuroimmune response; however, we also highlight significant cohort variation although burden levels were relatively low and below 0.5% for all regions apart from the hippocampus.…”
Section: Discussionsupporting
confidence: 72%
“…Detailed information about the cohort, brain imaging and post-mortem brain samples can be found in a cohort update and brain protocol papers (14,15). DNAm from whole blood and 5 post-mortem brain tissues has been measured using Illumina Infinium HumanMethylation450 BeadChip array (16). Quality control and processing details are provided in Supplemental Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…DNAm was measured in 5 brain regions (hippocampus - BA35, dorsolateral prefrontal cortex – BA46, primary visual cortex - BA17, anterior cingulate cortex - BA24, ventral/lateral inferior temporal cortex - BA20/21) from post-mortem brain samples of 14 LBC1936 individuals, with one sample missing from hippocampus. Tissue acquisition and processing details are detailed in Stevenson et al (16). Using blood-DNAm measured at wave 1 and brain-DNAm data, exploratory EWAS analyses were performed (CpG ∼ age + sex + smoking).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the relationship between DNA methylation patterns of ageing and inflammation in the blood and in the brain, Stevenson et al performed a matched analysis of DNA methylation data from blood and specific post-mortem brain regions from 14 individuals aged 70-79 years. This study, although limited by small sample size, identified potential vulnerability of the hippocampus, evidenced by ageing-related DNA methylation signatures (Stevenson et al, 2022). In a comprehensive, systematic review of the association between CSF protein markers of synapse loss and neuronal injury with cognition, Saunders et al come to the conclusion that due to substantial heterogeneity, no formal conclusions can be drawn, but suggest that neurofilament-light may be associated with worse cognition in AD, frontotemporal dementia and typical cognitive ageing, whereas the cerebrospinal fluid level of neurogranin is associated with cognition in those with AD-like biomarker profiles and neuronal pentraxin-2 correlates with cognition across dementia syndromes.…”
Section: Clinical Research and Biomarkersmentioning
confidence: 98%